2016
DOI: 10.24014/jush.v24i2.1525
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ruqyah Syar’iyyah on Physical Disease Treatment in Riau Province

Abstract: Ruqyah Syar'iyyah is one of Sunnah Prophet Muhammad in treating diseases and disorders syaithan, that is by reciting Al-Qur'an verses and praying. Most Muslims understand that ruqyah Syar'iyyah is only effectively treat non-medical disease or illness caused by psychiatric disorders and jin, whereas medical illness to be treated by medical means, Though al-Qur'an Surat al-Isra' verses 82 mentions that al-Qur'an is as a bidder (a cure) and a mercy for believers without distinction of medications for non-medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Ruqyah is effectively used in the treatment of patients with mental and physical disorders in ruqyah clinics in many districts in Indonesia. 44,46 Ruqyah is also practiced in certain places that provide official medical treatment and on television and YouTube in Indonesia. 47 In Saudi Arabia, ruqyah (roqia or ruqia) is commonly used by patients with many acute and chronic disorders such as eczema, mood disorders, and psychiatric conditions including anxiety, depression, and suicide ideations.…”
Section: Ruqyah: From Past To Presentmentioning
confidence: 99%
“…Ruqyah is effectively used in the treatment of patients with mental and physical disorders in ruqyah clinics in many districts in Indonesia. 44,46 Ruqyah is also practiced in certain places that provide official medical treatment and on television and YouTube in Indonesia. 47 In Saudi Arabia, ruqyah (roqia or ruqia) is commonly used by patients with many acute and chronic disorders such as eczema, mood disorders, and psychiatric conditions including anxiety, depression, and suicide ideations.…”
Section: Ruqyah: From Past To Presentmentioning
confidence: 99%
“…6 Many neuropsychiatric disorders such as mental problems, drugs addiction, headache with or without other symptoms and signs, pain due to cancer, and other part of body have been successfully treated with ruqyah applications. 7 Hashim et al 8 reported that there were various Islamic drug rehabilitation centers in Malaysia, and majority of them used healing ayats. Shifa ayats play an important role in managing stress among drug addicts.…”
mentioning
confidence: 99%
“…Ruqyah has also been known as having therapeutic effect of some cases of physical diseases as in case studies in Indonesia of a person with acute skin diseases and a person with stomach ulcer. Both persons had unsuccessful results after undergoing modern medical treatment but had very significant improvement after ruqyah [17]. A study in Malaysia on five cases of patients with psychological disorders and physical ailments found out that ruqyah brought positive results [18].…”
Section: Discussionmentioning
confidence: 99%